Implementation of Cryptographic Approach for Image Transmission with Security - SandhyaRani, M.; Sivaprasad, T. (International Journal of Engineering and Technology, 2018)
In this paper an approach for secured transmission of images and its implementation is being proposed.Â  The proposed method proves to be better compared to various presently existing cryptographic algorithms. The basic application of this algorithm is to provide secured transmission of digital images for various multimedia usages. These encrypted messages can further be used for compact storage of information of patient details which are very much confidently for patient centric approach. The results of the implementation show that the computation time is faster comparatively and it is highly secured and also efficient method for image transmission. The input for demonstration is taken as Lena image on which the Elliptic Curve Cryptography method is applied. The major advantage of this approach is reduced key size.Â Â